2008
DOI: 10.1080/00015458.2008.11680321
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Balloon Angioplasty of Renovascular Hypertension in Pediatric Cases

Abstract: PTRA can be safely performed resulting in excellent angiographic and clinical results. It should be first choice in renal artery stenosis in pediatric age when medical treatment fails to control renovascular hypertension or renal function is decreasing although initial results might be not encouraging in NF1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
1
17
2
Order By: Relevance
“…This concern was also expressed in other study (23). Restenosis, accounting for poor blood pressure control, was detected in nine of 22 patients (40.9%) in this study, giving a prevalence similar to that reported in a previous study (35%, n=20) (16). Neointima formation and recoil of immature renal arteries are responsible for restenosis (21).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This concern was also expressed in other study (23). Restenosis, accounting for poor blood pressure control, was detected in nine of 22 patients (40.9%) in this study, giving a prevalence similar to that reported in a previous study (35%, n=20) (16). Neointima formation and recoil of immature renal arteries are responsible for restenosis (21).…”
Section: Discussionsupporting
confidence: 72%
“…However, 27.3% (6/22) of children with renovascular hypertension failed to respond to PTRA. The success rate of PTRA for pediatric renovascular hypertension varies from 48.5% to 100% (8,16,17). The outcome of PTRA may be influenced by many factors, such as patient age, etiology, distribution of lesions, length and severity of lesions, and impairment degree of the target organ.…”
Section: Discussionmentioning
confidence: 99%
“…Bayrak et al 19 from Turkey reported their experience of using PTA in 20 children with RAS, with a success rate of 100%. The underlying aetiologies in their children were Takayasu arteritis in 12, FMD in 5 and NF1 in 3 cases.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Surgical reconstruction or endovascular therapy With a high initial success rate, endovascular procedures seem attractive for TARAS. 18,19 However, although encouraging midterm to long-term results have been reported sporadically, 20,21 most believe that the restenosis after angioplasty or stenting is common. Bayrak et al 19 performed PTA in 12 TARAS patients with a technical success rate of 100%, but restenosis was observed in five patients during 55.7 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%